Failure rate among the students of Universiti Islam Selangor: the case of Faculty of Management and Muamalah - Norziah Othman; Norhanizah Johari (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Education plays a vital role in human capital development. Issues on failure rate among the university students became a serious concern of Higher Learning Institutions (HLIs). This study presented the result of a recent analysis of the Selangor Islamic University by identifying factors of failures among the students of the Faculty of Management and Muamalah. This paper analyzes a specific case of university student failure rate in the Department of Accounting and Finance, Department of Economics and Management and Department of English Studies and Communication. Data was collected by using the overall results of subject for session I 2022/2023. The finding indicates that students’ failure is a complex phenomenon that depends on various factors such as; lack of discipline, low commitment and bad performance during the final examinations. Previous results of last academic session showed that the students are more likely to fail their subjects because of their low commitment during the class session. It is found that more than 10% failure rate were recorded especially for calculation subjects. Furthermore, it is found that the failure rate of the Diploma students has different causes as compared to the first-degree level students. The main causes of failure among students are: internal factors (attitude, commitment, lack of disciplines) and external factors (lecturer’s teaching approach and pedagogical).